Comfortable medical nursing pad with multi-layer structure and preparation process of comfortable medical nursing pad
Through the multi-layer structural design, combined with non-woven fabrics, porous materials, cellulose gels and fluff pulp fibers, the water absorption and diffusion performance of the care pad is improved, and the problem of insufficient absorption capacity of the traditional care pad is solved, achieving more efficient liquid management and better use comfort.
Patent Information
- Application Number
- CN202510329867.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Traditional care pads have weak absorption capacity and cannot absorb a large amount of body fluids quickly, which can easily lead to liquid respiration and increase the risk of skin damage and infection.
The multi-layer structure design adopts a multi-layer non-woven fabric, a three-dimensional porous material of the composite core layer, a cellulose gel and fuzz fiber structure, and a polyethylene film material of the bottom layer. Through the combination and treatment of these materials, water absorption and diffusion properties are improved.
It realizes rapid penetration and dispersion of liquids, reduces surface liquid accumulation, quickly absorbs and maintains a large amount of liquids, prevents back seepage, keeps the pads dry, reduces the risk of skin damage and infection, and improves absorption efficiency and comfort.
Smart Images

Figure CN119837707A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary products, and in particular to a comfortable medical nursing pad with a multi-layer structure and a preparation process thereof. Background Art
[0002] As an important auxiliary product in medical care, nursing pads are widely used in various scenarios such as patient care, surgical assistance, and wound care. Their main function is to absorb and isolate body fluids, keep the patient's skin dry, reduce the risk of skin infection, and facilitate medical staff to perform nursing operations. Their design and preparation process are directly related to the patient's experience and nursing effect.
[0003] Traditional nursing pads usually use simple cotton fibers or ordinary non-woven fabrics as the main material. Their absorption capacity is relatively weak and they cannot quickly absorb large amounts of body fluids. This can easily lead to liquid back-seepage, causing the patient's skin to remain moist for a long time, increasing the risk of skin damage and infection.
[0004] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention
[0005] The present invention overcomes the shortcomings of the prior art and provides a multi-layered comfortable medical nursing pad and a preparation process thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a multi-layered comfortable medical nursing pad, which comprises, from top to bottom: A top layer, wherein the top layer is a skin-friendly layer and is made of a non-woven fabric material; A composite core layer, wherein the composite core layer is a water-absorbing and diffusing layer, comprising a support structure of a three-dimensional porous material, a cellulose gel structure embedded in the three-dimensional porous material, and a fluff pulp fiber structure mixed in the three-dimensional porous material; The bottom layer is an air-proof layer and is made of a polyethylene film material.
[0007] In a preferred embodiment of the present invention, the thickness of the top layer is 0.1-0.3 mm; the thickness of the composite core layer is 1-3 mm; and the thickness of the bottom layer is 0.02-0.05 mm.
[0008] The present invention provides a preparation process of a multi-layered comfortable medical nursing pad, comprising the following steps: S1. Dissolving a bio-based polymer material in water to obtain a bio-based polymer colloidal solution of a certain concentration, pre-treating the solution at low temperature, freeze-drying the solution to obtain a bio-based polymer porous material, and performing calcium salt replacement treatment to form a bio-based polymer calcium porous material; S2, soaking the bio-based polymer calcium porous material in a surfactant, pre-treating it at low temperature, and then freeze-drying it to obtain a flexible bio-based polymer calcium porous material; S3, subjecting a cellulose fiber suspension of a certain concentration to ultrasonic treatment, dissolving an oxidant in water to obtain an oxidant solution of a certain concentration, and adding the oxidant solution to the cellulose fiber suspension after ultrasonic treatment, adjusting the pH to 4-5 and stirring once, adding ethylene glycol and stirring twice, dialyzing in water, and freeze-drying to obtain aldehyded cellulose fibers; S4, mixing the aldehyded cellulose fiber solution and the carboxymethyl chitosan solution, centrifuging, and standing in a constant temperature incubator to form a cellulose gel; S5, stirring the flexible bio-based polymer calcium porous material and the cellulose gel evenly, ultrasonically treating them, and fully mixing them with the fluff pulp fibers, spreading them into a web, and obtaining a composite core layer; S6. Use polyethylene film as the bottom layer and non-woven fabric as the top layer, place them on the bottom and top of the composite core layer respectively, heat-press and laminate them, and cut them to obtain a multi-layer structured comfortable medical nursing pad.
[0009] In a preferred embodiment of the present invention, in the step S1, the bio-based polymer material is one of sodium alginate or polylactic acid; the concentration of the bio-based polymer colloidal solution is 1.5~3 wt%; the pretreatment temperature is -5~-15°C, and the time is 20~24 h; the freeze-drying temperature is -30~-50°C, and the time is 24~48 h.
[0010] In a preferred embodiment of the present invention, in step S1, the replacement process specifically includes the following steps: The sodium alginate porous material is immersed in a 2-5 wt% calcium chloride / ethanol solution at room temperature for 4-8 h, and dried at 70-80 °C to constant weight to obtain a calcium alginate porous material, wherein the mass ratio of the sodium alginate porous material to the calcium chloride / ethanol solution is 1:3-6.
[0011] In a preferred embodiment of the present invention, in step S1, the replacement process specifically includes the following steps: The polylactic acid porous material is treated in an 8-15 wt% sodium hydroxide solution at a temperature of 80-100°C for 6-12 h to obtain sodium lactate, and the sodium lactate and calcium chloride with a molar ratio of 2:1 are magnetically stirred for 1-2 h at room temperature and centrifuged to obtain a calcium lactate porous material, wherein the mass ratio of the polylactic acid porous material to the sodium hydroxide solution is 1:4-8.
[0012] In a preferred embodiment of the present invention, in the step S2, the surfactant is one of glycerol or glycerol random polyether; the soaking time is 2 to 3 hours; the pretreatment temperature is -5 to -15 ° C, and the time is 20 to 24 hours; the freeze-drying temperature is -30 to -50 ° C, and the time is 24 to 48 hours; the mass ratio of the bio-based polymer calcium porous material to the surfactant is 1:3 to 8.
[0013] In a preferred embodiment of the present invention, in step S3, the cellulose fiber is one of nanocellulose fiber or bamboo charcoal fiber, the concentration of the cellulose fiber suspension is 0.8-1.5 wt %; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 1~3 h; the oxidant is one of potassium permanganate or sodium periodate, and the concentration of the oxidant solution is 10~15 wt%; the time of the first stirring is 3~6 h, and the time of the second stirring is 20~50 min; the temperature of the freeze-drying is -30~-50 ℃, and the time is 24~48 h; the mass ratio of the cellulose fiber suspension, the oxidant solution and the ethylene glycol is 1:0.1~0.3:0.07~0.12.
[0014] In a preferred embodiment of the present invention, in the step S4, the concentration of the aldehyded cellulose fiber solution is 0.8~1.5 wt%, the concentration of the carboxymethyl chitosan solution is 2~5 wt%, and the mass ratio of the aldehyded cellulose fiber solution to the carboxymethyl chitosan solution is 1:1; the centrifugation time is 20~40 min; the temperature of the static treatment is 35~50°C, and the time is 20~25 h.
[0015] In a preferred embodiment of the present invention, in the step S5, the mass ratio of the flexible bio-based macromolecular calcium porous material, the cellulose gel and the fluff pulp fiber is 1:0.08-0.16:0.6-0.8; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 15~30 min.
[0016] The present invention solves the defects existing in the background technology and has the following beneficial effects: The present invention provides a comfortable medical nursing pad with a multi-layer structure. By utilizing a three-dimensional porous material as the supporting structure of a composite core layer and embedding a cellulose gel structure, the specific surface area thereof is significantly improved. When liquid contacts the top layer, the liquid is allowed to quickly penetrate and disperse, reducing the accumulation of liquid on the surface, and can quickly absorb and retain a large amount of liquid to form a gel-like substance, effectively locking the liquid to prevent backseepage and keeping the pad surface dry. At the same time, the mixed fluff pulp fiber structure can be combined to form a graded pore system of micropores and macropores, which accelerates the lateral diffusion of liquid by capillary action, relieves the swelling pressure of cellulose gel, prevents local saturation, and achieves a dynamic balance of liquid absorption, diffusion and storage, thereby improving the overall absorption efficiency and comfort, avoiding the patient's skin from being in a wet state for a long time, and reducing the risk of skin damage and infection.
[0017] In the preparation process of the present invention, a high-strength porous skeleton is constructed by cross-linking bio-based polymer materials with calcium salts, and a surfactant is used to achieve flexible processing of the material, so that it has a certain water absorption performance, while improving the flexibility and elasticity of the material, increasing the fit and shape retention performance, and at the same time, the embedded cellulose gel can absorb the exudate to form a hydrogel phase, effectively lock the liquid to prevent backseepage, and further enhance the water absorption effect of the nursing pad. The mixed fluff pulp fiber can improve the diffusion effect of the liquid phase, prevent local swelling and saturation, and achieve a dynamic balance of liquid absorption, diffusion and storage, so that it has excellent water absorption rate and water absorption effect, thereby achieving better comfort in use.
[0018] In the preparation process of the present invention, by precisely controlling the ultrasonic treatment time during compounding of the core layer material, it is possible to achieve full stretching of the molecular chains and stabilization of the dynamic cross-linking network, making the molecular chains more dispersed and uniform, which helps to increase the specific surface area and porosity of the material, thereby improving the water absorption rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 is an overall separation structure diagram of a preferred embodiment of the present invention; Figure 2 is a schematic diagram of the composite core structure of a preferred embodiment of the present invention; In the figure: 1, top layer; 2, composite core layer; 21, support structure; 22, cellulose gel structure; 23, fluff pulp fiber structure; 3, bottom layer. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0022] like Figure 1 and Figure 2 As shown, a multi-layer comfortable medical nursing pad includes, from top to bottom: a top layer 1, wherein the top layer 1 is a skin-friendly layer made of a non-woven fabric material; a composite core layer 2, wherein the composite core layer 2 is a water-absorbing and diffusion layer, comprising a support structure 21 of a three-dimensional porous material, a cellulose gel structure 22 embedded in the three-dimensional porous material, and a fluff pulp fiber structure 23 mixed in the three-dimensional porous material; a bottom layer 3, wherein the bottom layer 3 is an anti-permeability air layer made of a polyethylene film material.
[0023] It should be noted that the thickness of the top layer 1 is 0.1~0.3 mm; the thickness of the composite core layer 2 is 1~3 mm; the thickness of the bottom layer 3 is 0.02~0.05 mm; the top layer 1 made of non-woven fabric material can effectively reduce the friction between the skin and the care pad, providing a comfortable use experience, while allowing the skin to maintain a certain breathability and reduce moisture; the bottom layer 3 made of polyethylene film material can ensure that the liquid absorbed by the composite core layer 2 will not leak onto the mattress or clothing, keeping the environment clean and dry; the composite core layer 2 uses a three-dimensional porous material as the supporting structure 21, and its specific surface area is significantly improved, providing a good liquid diversion channel and storage space, allowing the liquid to quickly penetrate and disperse, reducing the accumulation of surface liquid, and improving the absorption efficiency. At the same time, the cellulose gel structure 22 embedded in the supporting structure 21 has excellent liquid absorption capacity, can quickly absorb and retain a large amount of liquid, form a gel-like substance, effectively lock the liquid to prevent backseepage, and keep the pad surface dry. The fluff pulp fiber structure 23 mixed in the three-dimensional porous material has good inter-fiber gaps, so that they are combined to form a hierarchical pore system of micropores and macropores, and use capillary action to accelerate the lateral diffusion of liquid, relieve the swelling pressure of cellulose gel, prevent local saturation, and achieve a dynamic balance of liquid absorption, diffusion and storage, thereby improving the overall absorption efficiency and comfort.
[0024] A preparation process of a multi-layered comfortable medical nursing pad comprises the following steps: S1. Dissolving a bio-based polymer material in water to obtain a bio-based polymer colloidal solution of a certain concentration, pre-treating the solution at low temperature, freeze-drying the solution to obtain a bio-based polymer porous material, and performing calcium salt replacement treatment to form a bio-based polymer calcium porous material; S2, soaking the bio-based polymer calcium porous material in a surfactant, pre-treating it at low temperature, and then freeze-drying it to obtain a flexible bio-based polymer calcium porous material; S3, subjecting a cellulose fiber suspension of a certain concentration to ultrasonic treatment, dissolving an oxidant in water to obtain an oxidant solution of a certain concentration, and adding the oxidant solution to the cellulose fiber suspension after ultrasonic treatment, adjusting the pH to 4-5 and stirring once, adding ethylene glycol and stirring twice, dialyzing in water, and freeze-drying to obtain aldehyded cellulose fibers; S4, mixing the aldehyded cellulose fiber solution and the carboxymethyl chitosan solution, centrifuging, and standing in a constant temperature incubator to form a cellulose gel; S5, stirring the flexible bio-based macromolecular calcium porous material and the cellulose gel evenly, ultrasonically treating them, and fully mixing them with the fluff pulp fibers, spreading them into a web, and obtaining a composite core layer 2; S6. Use a polyethylene film as the bottom layer 3 and a non-woven fabric as the top layer 1, place them on the bottom and top of the composite core layer 2 respectively, heat-press and laminate them, and cut them to obtain a multi-layer structured comfortable medical nursing pad.
[0025] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.
[0026] In some specific embodiments, in step S1, the bio-based polymer material is one of sodium alginate or polylactic acid; the concentration of the bio-based polymer colloidal solution is 1.5~3 wt%; the pretreatment temperature is -5~-15°C, and the time is 20~24 h; the freeze-drying temperature is -30~-50°C, and the time is 24~48 h.
[0027] In some specific implementations, in step S1, the replacement process specifically includes the following steps: The sodium alginate porous material is immersed in a 2-5 wt% calcium chloride / ethanol solution at room temperature for 4-8 h, and dried at 70-80 °C to constant weight to obtain a calcium alginate porous material, wherein the mass ratio of the sodium alginate porous material to the calcium chloride / ethanol solution is 1:3-6.
[0028] In some specific implementations, in step S1, the replacement process specifically includes the following steps: The polylactic acid porous material is treated in an 8-15 wt% sodium hydroxide solution at a temperature of 80-100°C for 6-12 h to obtain sodium lactate, and the sodium lactate and calcium chloride with a molar ratio of 2:1 are magnetically stirred for 1-2 h at room temperature and centrifuged to obtain a calcium lactate porous material, wherein the mass ratio of the polylactic acid porous material to the sodium hydroxide solution is 1:4-8.
[0029] In some specific embodiments, in step S2, the surfactant is one of glycerol or glycerol random polyether; the soaking time is 2 to 3 h; the pretreatment temperature is -5 to -15 °C, and the time is 20 to 24 h; the freeze-drying temperature is -30 to -50 °C, and the time is 24 to 48 h; the mass ratio of the bio-based polymer calcium porous material to the surfactant is 1:3 to 8.
[0030] In some specific embodiments, in step S3, the cellulose fiber is one of nanocellulose fiber or bamboo charcoal fiber, the concentration of the cellulose fiber suspension is 0.8-1.5 wt %; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 1~3 h; the oxidant is one of potassium permanganate or sodium periodate, and the concentration of the oxidant solution is 10~15 wt%; the first stirring time is 3~6 h, and the second stirring time is 20~50 min; the freeze-drying temperature is -30~-50 ℃, and the time is 24~48 h; the mass ratio of cellulose fiber suspension, oxidant solution and ethylene glycol is 1:0.1~0.3:0.07~0.12.
[0031] In some specific embodiments, in step S4, the concentration of the aldehyde-modified cellulose fiber solution is 0.8-1.5 wt %, the concentration of the carboxymethyl chitosan solution is 2-5 wt %, and the mass ratio of the aldehyde-modified cellulose fiber solution to the carboxymethyl chitosan solution is 1:1; the centrifugation time is 20-40 min; the temperature of the static treatment is 35-50 ° C, and the time is 20-25 h.
[0032] In some specific embodiments, in step S5, the mass ratio of the flexible bio-based polymer calcium porous material, the cellulose gel and the fluff pulp fiber is 1:0.08-0.16:0.6-0.8; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 15~30 min.
[0033] In order to further make the purpose and effect of the present invention simple and easy to understand, the present invention is further described in conjunction with the following specific examples and comparative examples. Example 1
[0034] A preparation process of a multi-layered comfortable medical nursing pad comprises the following steps: S1. Dissolve sodium alginate in water to obtain a sodium alginate colloidal solution with a concentration of 2 wt%, freeze pre-treat at -15 °C for 24 h, and freeze-dry at -35 °C for 48 h to obtain a sodium alginate porous material, and soak the sodium alginate porous material in a 3 wt % calcium chloride / ethanol solution at room temperature for 6 h, and dry at 80 °C to constant weight to obtain a calcium alginate porous material, wherein the mass ratio of the sodium alginate porous material to the calcium chloride / ethanol solution is 1:5; S2, soaking the calcium alginate porous material in glycerol for 3 h, pre-freezing it at -15 °C for 24 h, and freeze-drying it at -35 °C for 48 h to obtain a flexible calcium alginate porous material, wherein the mass ratio of the calcium alginate porous material to the glycerol is 1:6; S3, a bamboo charcoal fiber suspension with a concentration of 1 wt% was heated at 1 W / cm 2 The power was set to 10000, ultrasonic treatment was performed for 2 h, potassium permanganate was dissolved in water to obtain a potassium permanganate solution with a concentration of 12 wt%, and the solution was added to the bamboo charcoal fiber suspension after ultrasonic treatment, the pH was adjusted to 4.5 and stirred for 4 h, ethylene glycol was added and stirred for 30 min, and after dialysis in water, the solution was freeze-dried at -40 °C for 24 h to obtain aldehyde-modified bamboo charcoal fibers, wherein the mass ratio of bamboo charcoal fiber suspension, potassium permanganate solution and ethylene glycol was 1:0.2:0.08; S4, mixing equal volumes of aldehyde-modified bamboo charcoal fiber solution with a concentration of 1.2 wt% and carboxymethyl chitosan solution with a concentration of 3 wt%, centrifuging for 30 min, and placing in a constant temperature incubator at 45 °C for 20 h to form bamboo charcoal cellulose gel; S5. Stir the flexible calcium alginate porous material and bamboo charcoal cellulose gel evenly at 2 W / cm 2 The power was ultrasonically treated for 20 min and fully mixed with the fluff pulp fiber, wherein the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber was 1:0.11:0.7, and spread into a net to obtain a composite core layer 2; S6. Use polyethylene film as the bottom layer 3 and non-woven fabric as the top layer 1, place them at the bottom and top of the composite core layer 2 respectively, hot-press and laminate at 110°C for 1.5 s, cut into 80*90 cm, and obtain a multi-layer structure comfortable medical nursing pad with a top layer 1 thickness of 0.1 mm, a composite core layer 2 thickness of 2 mm, and a bottom layer 3 thickness of 0.04 mm. Example 2
[0035] This embodiment is basically the same as Embodiment 1, except that the bio-based polymer material is polylactic acid, and the specific step of S1 is as follows: polylactic acid is dissolved in water to obtain a polylactic acid colloidal solution with a concentration of 2 wt%, and the solution is pre-frozen at -15 °C for 24 h, and freeze-dried at -35 °C for 48 h to obtain a polylactic acid porous material, and the polylactic acid porous material is treated in an 8 wt% sodium hydroxide solution at 80 °C for 8 h to obtain sodium lactate, and sodium lactate and calcium chloride with a molar ratio of 2:1 are magnetically stirred at room temperature for 2 h, and centrifuged to obtain a calcium lactate porous material, wherein the mass ratio of the polylactic acid porous material to the sodium hydroxide solution is 1:6. Example 3
[0036] This embodiment is basically the same as Embodiment 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.16:0.6. Example 4
[0037] This embodiment is basically the same as Embodiment 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.08:0.8. Example 5
[0038] This embodiment is substantially the same as Embodiment 1, except that in step S5, the ultrasonic treatment time is 15 min. Example 6
[0039] This embodiment is substantially the same as Embodiment 1, except that in step S5, the ultrasonic treatment time is 30 min.
[0040] Comparative Example 1 Commercially available: Linyi Yunlu Biotechnology Co., Ltd. - model YXR-CRHLD adult care pad; main components include: top layer composed of non-woven fabric, core layer composed of plush pulp and polymer absorbent resin (SAP), bottom layer composed of PE film; size is 80*90 cm, top layer thickness is 0.1 mm; composite core layer thickness is 2 mm; bottom layer thickness is 0.04 mm.
[0041] Comparative Example 2 This comparative example is basically the same as Example 1, with the difference that: there are no steps S3 and S4, and step S5 is specifically: fully mixing the flexible calcium alginate porous material with the fluff pulp fiber, wherein the mass ratio of the flexible calcium alginate porous material to the fluff pulp fiber is 1:0.7, spreading it into a net, and obtaining a composite core layer 2.
[0042] Comparative Example 3 This comparative example is basically the same as Example 1, except that: Step S5 specifically comprises: stirring the flexible calcium alginate porous material and the bamboo charcoal cellulose gel evenly at 2 W / cm 2 The power was 20 minutes of ultrasonic treatment, wherein the mass ratio of the flexible calcium alginate porous material to the bamboo charcoal cellulose gel was 1:0.11, and the composite core layer 2 was obtained by spreading it into a net.
[0043] Comparative Example 4 This comparative example is substantially the same as Example 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.05:0.7.
[0044] Comparative Example 5 This comparative example is basically the same as Example 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.19:0.7.
[0045] Comparative Example 6 This comparative example is basically the same as Example 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.11:0.5.
[0046] Comparative Example 7 This comparative example is basically the same as Example 1, except that in step S5, the mass ratio of the flexible calcium alginate porous material, the bamboo charcoal cellulose gel and the fluff pulp fiber is 1:0.11:1.
[0047] Comparative Example 8 This comparative example is substantially the same as Example 1, except that in step S5, the ultrasonic treatment time is 10 min.
[0048] Comparative Example 9 This comparative example is substantially the same as Example 1, except that in step S5, the ultrasonic treatment time is 35 min.
[0049] Performance testing: The medical nursing pads prepared in Examples 1-6 and Comparative Examples 1-9 were tested for absorption rate. The results are shown in Table 1.
[0050] Absorption rate test: refer to ISO 15226-1 "Test method for absorption performance of disposable absorbent products", place a 500 mL measuring cylinder in the middle of the nursing pad, pour in 300 mL of artificial urine, and record the time required for the liquid to be completely absorbed by the nursing pad.
[0051] Table 1: Performance test results
[0052] It can be seen from Table 1 that: By comparing Example 1 with Comparative Example 1, it can be seen that by using calcium salt to crosslink bio-based polymer materials to construct a high-strength porous skeleton, and using surfactants to achieve flexible processing of the material, it has a certain water absorption performance while improving the flexibility and elasticity of the material, increasing the fit and shape retention performance, and at the same time, with the chimeric cellulose gel, it can absorb the exudate to form a hydrogel phase, effectively lock the liquid to prevent back seepage, and further enhance the water absorption effect of the nursing pad. The mixed fluff pulp fiber can improve the diffusion effect of the liquid phase, prevent local swelling and saturation, and achieve a dynamic balance of liquid absorption, diffusion and storage, so that it has excellent water absorption rate and water absorption effect, thereby achieving better comfort in use. However, in traditional nursing pads, SAP particles rely on physical adsorption to lock liquid. After absorbing liquid, the particles are easy to agglomerate to form a gel barrier, which hinders liquid diffusion, thereby reducing the water absorption rate and effect.
[0053] By comparing Example 1 with Example 2, it can be seen that the bamboo charcoal cellulose gel forms a dynamic cross-linked network through the Schiff base reaction of formaldehyded cellulose and carboxymethyl chitosan, and the hydrogen bonds and covalent bonds in the network can simultaneously bind water molecules to form a stable hydrogel phase, lock the liquid and prevent backseepage; and the skeleton constructed by the fluff pulp fibers and the three-dimensional porous material adopted forms a macropore-micropore hierarchical structure, which accelerates liquid diffusion through the capillary gradient effect; by comparing Example 1 with Comparative Example 2, it can be seen that when the bamboo charcoal cellulose gel is removed, the molecular-level water-locking mechanism of the bamboo charcoal cellulose gel is lost, resulting in a decrease in liquid retention capacity and a decrease in liquid absorption efficiency; by comparing Example 1 with Comparative Example 3, it can be seen that after removing the fluff pulp fibers, the pore scale is only macropores, and the lateral diffusion rate of the liquid is reduced, resulting in a decrease in the liquid diffusion effect, thereby reducing the liquid absorption rate and effect.
[0054] By comparing Example 1, Example 3 and Example 4 with Comparative Examples 4-7, it can be learned that suitable flexible calcium alginate porous material, bamboo charcoal cellulose gel and fluff pulp fiber content can maintain excellent liquid absorption rate and effect; wherein, the bamboo charcoal cellulose gel forms a dynamic cross-linked network with carboxymethyl chitosan through aldehyde groups. When the ratio is unbalanced, excess gel will overfill the pores of the calcium alginate porous skeleton, resulting in decreased pore connectivity, weakened capillary force, and limited material swelling freedom. When the ratio is too low, the density of the dynamic cross-linked network is too low, and it is impossible to effectively lock liquid through hydrogen bonds and covalent bonds. The three-dimensional porous skeleton lacks gel support, and after liquid absorption, it is easy to cause pore collapse due to uneven swelling pressure, which blocks the liquid diffusion path and affects the water absorption effect. At the same time, excessive fluff pulp fibers will occupy the macropore space, resulting in failure of the macropore-micropore grading system, disappearance of the capillary gradient effect, and reduced lateral liquid diffusion rate. Too low a ratio leads to insufficient diffusion channels, and the diffusion of liquid in the composite core layer is limited, making it difficult to maintain pore stability and dynamic balance of liquid absorption.
[0055] By comparing Example 1, Example 5 and Example 6 with Comparative Examples 8 and Comparative Examples 9, it can be learned that by precisely controlling the ultrasonic treatment time when compounding the core layer material, it is possible to achieve full stretching of the molecular chains and stabilization of the dynamic cross-linking network, making the molecular chains more dispersed and uniform, which helps to increase the specific surface area and porosity of the material, thereby improving the water absorption rate; when the ultrasonic time is too short, the molecular chains are not fully stretched, resulting in local agglomeration and decreased pore connectivity. At the same time, too long an ultrasonic time can easily lead to breakage of the molecular chains inside the material and destroy the pore structure inside the material, making it uneven or blocked, thereby reducing the water absorption rate and effect.
[0056] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0057] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A multi-layered comfortable medical nursing pad, characterized in that: From top to bottom, they include: A top layer, wherein the top layer is a skin-friendly layer and is made of a non-woven fabric material; A composite core layer, wherein the composite core layer is a water-absorbing and diffusing layer, comprising a support structure of a three-dimensional porous material, a cellulose gel structure embedded in the three-dimensional porous material, and a fluff pulp fiber structure mixed in the three-dimensional porous material; The bottom layer is an air-proof layer and is made of a polyethylene film material.
2. A multi-layered comfortable medical nursing pad according to claim 1, characterized in that: The thickness of the top layer is 0.1-0.3 mm; the thickness of the composite core layer is 1-3 mm; and the thickness of the bottom layer is 0.02-0.05 mm.
3. A preparation process of a multi-layered comfortable medical nursing pad according to any one of claims 1-2, characterized in that: The following steps are involved: S1, dissolving the bio-based polymer material in water to obtain a bio-based polymer colloidal solution with a concentration of 1.5-3 wt%, pre-treating the solution at low temperature, freeze-drying the solution to obtain a bio-based polymer porous material, and performing calcium salt replacement treatment to form a bio-based polymer calcium porous material; S2, soaking the bio-based polymer calcium porous material in a surfactant, pre-treating it at low temperature, and then freeze-drying it to obtain a flexible bio-based polymer calcium porous material; S3, treating a cellulose fiber suspension having a concentration of 0.8-1.5 wt %, dissolving an oxidant in water to obtain an oxidant solution having a concentration of 10-15 wt %, adding the oxidant solution to the cellulose fiber suspension after the ultrasonic treatment, adjusting the pH to 4-5 and stirring once, adding ethylene glycol and stirring twice, dialyzing in water, and freeze-drying to obtain aldehyded cellulose fibers; S4, mixing the aldehyded cellulose fiber solution and the carboxymethyl chitosan solution, centrifuging, and standing in a constant temperature incubator to form a cellulose gel; S5, stirring the flexible bio-based macromolecular calcium porous material and the cellulose gel evenly, ultrasonically treating them, and fully mixing them with the fluff pulp fibers, spreading them into a web, and obtaining a composite core layer; S6. Use polyethylene film as the bottom layer and non-woven fabric as the top layer, place them on the bottom and top of the composite core layer respectively, heat-press and laminate them, and cut them to obtain a multi-layer structured comfortable medical nursing pad.
4. The preparation process of a multi-layered comfortable medical nursing pad according to claim 3, characterized in that: In step S1, the bio-based polymer material is one of sodium alginate or polylactic acid; the pretreatment temperature is -5~-15°C, and the time is 20~24 h; the freeze-drying temperature is -30~-50°C, and the time is 24~48 h.
5. The preparation process of a multi-layered comfortable medical nursing pad according to claim 4, characterized in that: In the step S1, the replacement process specifically includes the following steps: The sodium alginate porous material is immersed in a 2-5 wt% calcium chloride / ethanol solution at room temperature for 4-8 h, and dried at 70-80° C. to a constant weight to obtain a calcium alginate porous material.
6. The preparation process of a multi-layered comfortable medical nursing pad according to claim 4, characterized in that: In the step S1, the replacement process specifically includes the following steps: The polylactic acid porous material is treated in an 8-15 wt% sodium hydroxide solution at a temperature of 80-100°C for 6-12 h to obtain sodium lactate. Sodium lactate and calcium chloride with a molar ratio of 2:1 are magnetically stirred for 1-2 h at room temperature and centrifuged to obtain a calcium lactate porous material.
7. The preparation process of a multi-layered comfortable medical nursing pad according to claim 3, characterized in that: In the step S2, the surfactant is one of glycerol or glycerol random polyether; the soaking time is 2 to 3 hours; the pretreatment temperature is -5 to -15 ° C, and the time is 20 to 24 hours; the freeze-drying temperature is -30 to -50 ° C, and the time is 24 to 48 hours.
8. The preparation process of a multi-layered comfortable medical nursing pad according to claim 3, characterized in that: In the step S3, the cellulose fiber is one of nanocellulose fiber and bamboo charcoal fiber; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 1~3 h; the oxidant is one of potassium permanganate or sodium periodate; the time of the first stirring is 3~6 h, and the time of the second stirring is 20~50 min; the temperature of the freeze-drying is -30~-50℃, and the time is 24~48 h.
9. The preparation process of a multi-layered comfortable medical nursing pad according to claim 3, characterized in that: In the step S4, the concentration of the aldehyded cellulose fiber solution is 0.8-1.5 wt %, the concentration of the carboxymethyl chitosan solution is 2-5 wt %, and the mass ratio of the aldehyded cellulose fiber solution to the carboxymethyl chitosan solution is 1:1; the centrifugation time is 20-40 min; the temperature of the static treatment is 35-50 ° C, and the time is 20-25 h.
10. The preparation process of a multi-layered comfortable medical nursing pad according to claim 3, characterized in that: In the step S5, the mass ratio of the flexible bio-based macromolecular calcium porous material, the cellulose gel and the fluff pulp fiber is 1:0.08-0.16:0.6-0.8; the power of the ultrasonic treatment is 1-3 W / cm 2 , time is 15~30min.
Citation Information
Patent Citations
Sponge calcium alginate medical dressing, and preparation method
CN102258801A
Sodium alginate-sodium carboxymethylcellulose-chitosan wound dressing and preparation method thereof
CN104069537A
Medical nursing pad for preventing bedsore
CN106038073A
Natural polymer-based multi-layer compound medicinal dressing and preparation method thereof
CN106110367A
Preparation method of composite alginate agar impression material
CN109771305A
Cited By
Multi-layer composite medical water-absorbing shock insulator and preparation method thereof
CN121221368A
Anti-leakage multi-layer composite medical abdominal pad
CN121891187A